2015
DOI: 10.1098/rsbl.2015.0408
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting modification of soil fungal diversity associated with the introduction of rabbits to a remote sub-Antarctic archipelago

Abstract: During the late nineteenth century, Europeans introduced rabbits to many of the sub-Antarctic islands, environments that prior to this had been devoid of mammalian herbivores. The impacts of rabbits on indigenous ecosystems are well studied; notably, they cause dramatic changes in plant communities and promote soil erosion. However, the responses of fungal communities to such biotic disturbances remain unexplored. We used metabarcoding of soil extracellular DNA to assess the diversity of plant and fungal commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The ability to resample allows for measurement of change through time. Across studies, we found a range of 2–100 subsamples taken per plot (Drummond et al., ; Pansu et al., ). Although the number of subsamples was generally easily determined, it was hard to find out how that number of subsamples was selected.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to resample allows for measurement of change through time. Across studies, we found a range of 2–100 subsamples taken per plot (Drummond et al., ; Pansu et al., ). Although the number of subsamples was generally easily determined, it was hard to find out how that number of subsamples was selected.…”
Section: Resultsmentioning
confidence: 99%
“…Details about the extraction procedure are available in Supplementary material Appendix 1. Four primer pairs were used to amplify specifically the v8-9 region of the 16S rRNA gene in archaea (Taberlet et al 2018), the v5-6 region of the 16S rRNA gene in bacteria (Fliegerova et al 2014), the ITS1 in fungi (Fung02 in Pansu et al 2015, Taberlet et al 2018) and the P6 loop of the chloroplast trnL intron in vascular plants (Taberlet et al 2007). Four primer pairs were used to amplify specifically the v8-9 region of the 16S rRNA gene in archaea (Taberlet et al 2018), the v5-6 region of the 16S rRNA gene in bacteria (Fliegerova et al 2014), the ITS1 in fungi (Fung02 in Pansu et al 2015, Taberlet et al 2018) and the P6 loop of the chloroplast trnL intron in vascular plants (Taberlet et al 2007).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…Each sample was subdivided into two subsamples of 10 g each, which were used as DNA extraction replicates to allow for controlling amplification biases (Ficetola et al 2015). Four primer pairs were used to amplify specifically the v8-9 region of the 16S rRNA gene in archaea (Taberlet et al 2018), the v5-6 region of the 16S rRNA gene in bacteria (Fliegerova et al 2014), the ITS1 in fungi (Fung02 in Pansu et al 2015, Taberlet et al 2018) and the P6 loop of the chloroplast trnL intron in vascular plants (Taberlet et al 2007). For each marker, we conducted two PCRs per extraction replicate (i.e.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…The coevolutionary relationship between the soil microbiome and plants is well defined (Bonkowski et al 2009;Van Nuland et al 2016), and has been explored in the context of ecosystem restoration or recovery post-disturbance (Pansu et al 2015;Cavagnaro et al 2016;Hamonts et al 2017). Correlated succession of soil microbial and plant communities has also been shown from both natural succession and restoration interventions ( Fig.…”
Section: The Microbiome Rewilding Hypothesismentioning
confidence: 99%